2023
DOI: 10.1111/jocd.15580
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid microinjections versus tranexamic acid mesoneedling in the treatment of facial melasma: A randomized assessor‐blind split‐face controlled trial

Abstract: Background: Melasma is a hyperpigmentary disorder causing cosmetic disfigurement.We aimed to compare the efficacy and safety of tranexamic acid (TXA) microinjections with TXA mesoneedling for facial melasma.Methods: This randomized assessor-blind split-face controlled trial included patients with symmetric facial melasma. One side of the face received TXA (100 mg/ml) mesoneedling and the other side intradermal TXA microinjections. The interventions were repeated three times with 4-week intervals (weeks 0, 4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Three studies 12,22,34 compared microneedling with topical TXA to microinjections with TXA; the pooled analysis suggested that intradermal microinjections with TXA were more effective (overall effect, SMD = 1.94, 95% CI = 1.02–2.87; Figure S10). Due to less skin trauma, less pain, and shorter treatment sessions, patient satisfaction and tolerance of microneedling were higher 22,34 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies 12,22,34 compared microneedling with topical TXA to microinjections with TXA; the pooled analysis suggested that intradermal microinjections with TXA were more effective (overall effect, SMD = 1.94, 95% CI = 1.02–2.87; Figure S10). Due to less skin trauma, less pain, and shorter treatment sessions, patient satisfaction and tolerance of microneedling were higher 22,34 …”
Section: Resultsmentioning
confidence: 99%
“…In the 16 studies, 621 patients were included. Three studies 12,22,34 evaluated the efficacy and safety between microneedling and microinjection with TXA; four studies 21,[31][32][33] adopted microneedling with vitamin C in control; and three studies 20,24,26 used microneedling alone or with placebo in control; two 23,28 included 4% hydroquinone; two 25,29 used a laser with TXA; one 27 employed microneeding with platelet rich plasma (PRP); and one 30 included oral TXA.…”
Section: Study Information and Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we would like to voice our cordial thanks to Poostiyan et al 1 as a result of their hard work, once again. To reach a definitive conclusion, additional studies with larger sample sizes are needed to emphasize these conclusions.…”
mentioning
confidence: 87%
“…It was with great interest that we read the paper by Poostiyan et al 1 entitled “Tranexamic acid microinjections versus tranexamic acid mesoneedling in the treatment of facial melasma: A randomized assessor‐blind split‐face controlled trial” published on Journal of Cosmetic Dermatology . The authors found comparable improvement in modified Melasma Area and Severity Index (mMASI) scores with both Tranexamic acid (TXA) mesoneedling and TXA microinjections for the treatment of facial melasma.…”
mentioning
confidence: 99%